Incorporating SPE into MDA including middleware performance details into system models. - Verdickt, Tom (Software engineering notes.)
A typical feature of a distributed system is the heterogeneity of its components (their geographical spreading, using different programming languages and platform architectures, etc.). To solve some of the problems related to this heterogeneity, many distributed systems use communication middleware.This paper presents an MDA model transformation algorithm and tool for transforming a high-level Platform Specific Model (high-level PSM) to a low-level PSM by including the structural changes and the overhead of using CORBA as a middleware. The resulting PSM (a UML model annotated with performance information, using the UML performance profile) can be used for generating performance models of the system, using existing methods and tools.